Biomarkers of nanomaterials hazard from multi-layer data - Fortino Vittorio; Kinaret Pia Anneli Sofia; Fratello Michele; Serra Angela; Saarimäki Laura Aliisa; Gallud Audrey; Gupta Govind; Vales Gerard; Correia Manuel; Rasool Omid; Ytterberg Jimmy; Monopoli Marco; et al. (Nature Portfolio, 2022)
Nanomaterials have a range of potential applications, however, toxicity remains a concern, limiting application and requiring extensive testing. Here, the authors report on a predictive framework made using a range of tests linking materials properties with toxicity, allowing the prediction of toxicity from physiochemical and biological properties.There is an urgent need to apply effective, data-driven approaches to reliably predict engineered nanomaterial (ENM) toxicity. Here we introduce a predictive computational framework based on the molecular and phenotypic effects of a large panel of ENMs across multiple in vitro and in vivo models. Our methodology allows for the grouping of ENMs based on multi-omics approaches combined with robust toxicity tests. Importantly, we identify mRNA-based toxicity markers and extensively replicate them in multiple independent datasets. We find that models based on combinations of omics-derived features and material intrinsic properties display significantly improved predictive accuracy as compared to physicochemical properties alone.